(untitled) (Anwer Khan Modern Medical College Journal, 2018)
Background: Heavy metals like chromium compounds can be carcinogenic usually used in the tanning process during leather production. Chromium is an important health risk factor for the tannery workers which may enter the body by inhalation, ingestion and by direct cutaneous contact and cause several health problems of skin and respiratory tract. With the increase of unplanned industries, Bangladesh poses a new challenge to combat health hazards associated with heavy metal toxicity in soil. Objective: The present study was designed to find out possible toxic effects of heavy metals in soil and health hazards among the people residing at tannery industries area. Materials and Methods: This is a descriptive cross-sectional study and was carried out in two phases during the period of 1st November 2009 to 30 June 2010. In first phase the soil samples were taken from lagoons of Hazaribagh Thana of Dhaka city for laboratory test of heavy metals. In second phase, a total 190 respondents were interviewed using a semi-structured questionnaire to ascertain the common health problem around the tannery industries. Results: All the eight soil samples contained Cr, Mn, Ni, Fe, Pb, Cu, where as Cd was nil. Mean distributor of Cr, Mn, Ni, Fe, Pb and Cu was 43.1325, 354.2217, 28.6633, 22420.1867, 97.5833 and 53.4633 ppm respectively. 75.26% respondents stayed in the study area for six to ten years. Most of the respondents (75) were tannery workers. Total 52.85% households had toxicity related sickness in last six months. Among tannery workers most prevalent sickness were conjunctivitis (7.7%) and Dermatitis (6.7%). Regarding occurrence of clinical manifestations similar to Chromium toxicity in relation to staying in the study area, most of the households complained about allergy (39.2%) and abdominal discomfort (24.4%). Conclusion: Elevated levels of urinary and blood Chromium is associated with high morbidity among the tannery workers. Therefore bio-monitoring of the heavy metals in the exposed workers is considered as a useful tool. Anwer Khan Modern Medical College Journal Vol. 9, No. 1: Jan 2018, P 39-43